A TRLFS study on the complexation of Cm(III) and Eu(III) with 4-t-butyl-6,6′-bis-(5,6-diethyl-1,2,4-triazin-3-yl)-2,2′-bipyridine in a water/2-propanol mixture - Trumm, Sascha; Lieser, Georg; Foreman, Mark R. S. J.; Panak, Petra; Geist, Andreas; Fanghänel, Thomas (Dalton transactions, 2010)
The complexation of Cm(III) and Eu(III) with 4-t-butyl-6,6′-bis-(5,6-diethyl-1,2,4-triazin-3-yl)-2,2′-bipyridine (t-Bu-C2-BTBP) in water/2-propanol solution is studied. With increasing ligand concentration, 1 : 2 complexes [M(t-Bu-C2-BTBP)2(H2O)]3+ form from the solvated metal ions. The stability constants are log KCm(III) = 11.1 and log KEu(III) = 9.0. For both Cm(III) and Eu(III), the complexation reaction is both enthalpy and entropy driven. ΔHCm(III) is 11.7 kJ mol−1 more negative than ΔHEu(III), whereas the entropy difference is negligible. This is in good agreement with t-Bu-C2-BTBP's selectivity in liquid-liquid extraction.